ESCULPINDO ESCUTÁTÓRIAS NO GRUPO DE OUVIDORES “ENTRE NÓS” - Santos, Amanda Lovo dos (2022)
The objective of this research was to study, through the sharing of extended listening, the processes of health production in the "Entre Nós" group of voice-listeners. The team meetings were constituted in a remote format due to the requirements of social distancing, recommended by the public health agencies, aiming at containing the pandemic generated by COVID-19. Intending to follow these processes, the Cartography approach was used as a methodological proposal (PASSOS, KASTRUP e ESCÓSSIA, 2009). Its general purpose was to investigate what the voice-listeners produce in this group, based on the conception of their experiences, affections and encounters as a field in the production of knowledge, as well as the transformation of the observations made in narratives recorded in a logbook. Then, it was emphasized that experiencing the hearing of voices from the perspective of the ombudspersons themselves helps overcome a strictly biomedical model, stressing the power of creation and modification of reality through this experience, which reveals a production of health that is constantly ignored by the medical sciences.